Numerical investigation of thermal non-equilibrium effects of diatomic and polyatomic gases on the shock-accelerated square light bubble using a mixed-type modal discontinuous Galerkin method - Singh, Satyvir (2022)
In this article, a numerical investigation is carried out for analyzing the thermal non-equilibrium effects of diatomic and polyatomic gases on the flow dynamics of a shock-accelerated square light bubble. The simulation emphasis is placed on the flow morphology visualization, wave patterns, degree of thermal non-equilibrium, vorticity generation, and evolution of enstrophy as well as dissipation rate. A two-dimensional system of unsteady physical conservation laws derived from the Boltzmann-Curtiss kinetic equation of diatomic and polyatomic gases is solved by employing an in-house developed mixed-type modal discontinuous Galerkin method with uniform meshes. An explicit third-order SSP Runge-Kutta scheme is employed for the time discretization. The numerical results are compared with existing experimental results for validation, and they are found in good agreement. The results elucidate that the effects of thermal non-equilibrium, including different gas properties play a significant role during the interaction between an incident shock wave and a square light bubble. The effects of diatomic and polyatomic gases cause a significant change in flow morphology, resulting in complex wave patterns, vorticity generation, vortices formation, and bubble deformation. In comparison to monatomic gases, diatomic and polyatomic gases exhibit the formation of larger rolled-up vortex chains, different jet structure and large mixing zones. A detailed investigation on the effects of diatomic and polyatomic gases is explored using the vorticity generation, degree of non-equilibrium, the evolutions of enstrophy and dissipation rate. Finally, the effects of thermal non-equilibrium parameters, including temperature-dependent transport coefficient and bulk viscosity ratio, on the flow dynamics of the shock-accelerated square light bubble are comprehensively investigated.